2012
DOI: 10.1161/strokeaha.111.640102
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Experience on Eversion Versus Conventional Carotid Endarterectomy in Symptomatic Carotid Artery Stenosis

Abstract: Background and Purpose— Carotid endarterectomy (CEA) is beneficial in patients with symptomatic carotid artery stenosis. However, randomized trials have not provided evidence concerning the optimal CEA technique, conventional or eversion. Methods— The outcome of 563 patients within the surgical randomization arm of the Stent-Protected Angioplasty versus Carotid Endarterectomy in Symptomatic Patients (SPACE-1) trial was analyzed by surgical technique sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 33 publications
0
6
0
5
Order By: Relevance
“…Reports indicate that duplex ultrasound will result in revision of the endarterectomy in 2.3% of cases, but no studies have shown that this increases the technical success of a CEA. 13 Similarly, in the Stent-Protected Angioplasty vs Carotid Endarterectomy (SPACE-1) trial, eversion rather than patch angioplasty was not shown to be associated with worse long-term outcomes 14 and saved 16 minutes of Op time compared with using a patch in our model. Therefore, in a patient with cardiac disease, a surgeon could consider specific techniques to shorten the procedure and potentially to reduce cardiac MAEs.…”
Section: Discussionmentioning
confidence: 67%
“…Reports indicate that duplex ultrasound will result in revision of the endarterectomy in 2.3% of cases, but no studies have shown that this increases the technical success of a CEA. 13 Similarly, in the Stent-Protected Angioplasty vs Carotid Endarterectomy (SPACE-1) trial, eversion rather than patch angioplasty was not shown to be associated with worse long-term outcomes 14 and saved 16 minutes of Op time compared with using a patch in our model. Therefore, in a patient with cardiac disease, a surgeon could consider specific techniques to shorten the procedure and potentially to reduce cardiac MAEs.…”
Section: Discussionmentioning
confidence: 67%
“…Research Demirel and associates as advantages C-CEA informing about a greater 30 day risk of both stroke and death in patients treated with E-CEA technique (9% vs. 3%, p = 0.005) (8), unlike the other speaking the significantly lower morbidity and mortality (1.35% vs. 4%, p <0.005) (16) and a smaller number of CVI (0.9% vs. 2.9%, p <0.01) and mortality 1.8%, compared to 0.54%, P <0.05 (17), in a patient operated E-CEA technique. In contrast to these, some studies have recorded a statistically significant difference in the incidence of postoperative ICV and death in patients operated with these two operating techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The potential advantage of E-CEA is the fact that placing the patch at the same it is not necessary (8, 9, 10). …”
Section: Introductionmentioning
confidence: 99%
“…По данным исследований, несмотря на хорошие отдаленные результаты после эверсионной КЭ, частота периоперационных инсультов при данной методике встречается чаще, чем при выполнении классической КЭ [20,21]. Это обусловлено трудностями адекватной эндартерэктомии, риском расслоения интимы с развитием тромбоза сонной артерии, сложностями установки шунта при протяженном поражении ВСА [20,22].…”
Section: результатыunclassified